Search for diphoton resonances in the 66 to 110 GeV mass range using pp collisions at s = 13 TeV with the ATLAS detector - Aad, G; Abbott, B; Abeling, K; Abicht, NJ; Abidi, SH; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, BS; Adam Bourdarios, C; Adamczyk, L; et al. (Springer, 2025)
A search is performed for light, spin-0 bosons decaying into two photons in the 66 to 110 GeV mass range, using 140 fb−1 of proton-proton collisions at s = 13 TeV produced by the Large Hadron Collider and collected by the ATLAS detector. Multivariate analysis techniques are used to define event categories that improve the sensitivity to new resonances beyond the Standard Model. A model-independent search for a generic spin-0 particle and a model-dependent search for an additional low-mass Higgs boson are performed in the diphoton invariant mass spectrum. No significant excess is observed in either search. Mass-dependent upper limits at the 95% confidence level are set in the model-independent scenario on the fiducial cross-section times branching ratio into two photons in the range of 8 fb to 53 fb. Similarly, in the model-dependent scenario upper limits are set on the total cross-section times branching ratio into two photons as a function of the Higgs boson mass in the range of 19 fb to 102 fb.